Rehydration, pH, brix, titrable acidity and color variations of infrared and microwave dried European Cranberrybush - Taskin, O.; Izli, N.; İzli, Gökçen (Agrimedia Gmbh, 2019)
This work aims at investigating rehydration, pH, brix, titrable acidity and color in infrared and microwave drying of European Cranberrybush. Drying experiments were carried out at infrared temperature of 60, 70 and 80 degrees C and microwave power of 120 and 350 W. The results showed that both the infrared temperature and microwave power influenced the drying time. The slope of the higher infrared temperature or microwave power was found steeper in drying rate. Under the all drying experiments, good rehydration ratio was obtained. The maximum change of the brix and titrable acidity were determined by 350 W. In terms of pH, infrared dried at 60 degrees C samples had higher pH than fresh samples. By comparison colorimetric parameters (L*, a*, b* and C), being highest values were reached at 80 degrees C, whereas the lowest values were achieved at 350 W. In addition, the total color change (Delta E) of European Cranberrybush dried at infrared and microwave methods were found significantly different (P < 0.05).
Keywords: Drying rate; drying time; physico-chemical; Viburnum opulus L.